Experimental study of discharge rate fluctuations in a silo with different hopper geometries - Uñac, Rodolfo Omar (2012)
An experimental study of the flow of quartz particles with two different mean size was performed on a 3D silo at the scale of the laboratory. Two kinds of hopper geometry were used for the cylindrical silo: flat-bottomed and conical. The diameter of the outlet was varied. The dependence of the flow rate and its fluctuations on the silo geometry and outlet size was studied. The Beverloo equation was satisfied in all cases studied and the dependence of its parameters on the silo geometry and on the particle size was analyzed. Using a Fourier analysis, we found a characteristic frequency which varied with the outlet diameter and was virtually independent of the hopper geometry.